MiR-126-3p promotes the development and progression of preeclampsia through the inactivation of the PI3K/AKT pathway - Pingping Zhu; Yanjun Hu; Jiaying Shen; Jianqiong Zheng; Tingting Liao; Yeping Wang (Molecular Biology Reports, 2026)

Selenium alleviates Staphylococcus aureus-induced mastitis by modulating mitochondrial dynamics and inhibiting the ROS/NLRP3/Pyroptosis pathway - Xue Qi; Yanjun Hu; Jinghan Yang; Mingxuan Jiang; Junhao Zhang; Yanting Du; Changmin Hu (Molecular Biology Reports, 2026)

Quaternary evaporite sedimentation and potassium enrichment mechanism in Mahai Salt Lake, Qaidam Basin - Zihao Cui; Yanjun Zhao; Chenglin Liu; Pengyu Long; Yufei Hu; Ju Jiao; Jingjing Liu (Sedimentary Geology, 2026)

Holocene environmental changes recorded by magnetic parameters of sediments in the Yangtze River Delta and implications for prehistoric cultural development - Guiye Zhang; Longsheng Wang; Shouyun Hu; Mingming Ma; Jiawen Zhao; Yanjun Ge; Lin Zeng; Xianbin Liu (Estuarine, Coastal and Shelf Science, 2026)

Developing Si/Al-rich biochar for higher incorporation in building materials: Enhanced mechanics and reduced carbon emissions - Gang Huang; Lei Wang; Liang Chen; Yanjun Hu; Kitae Baek; Shurong Wang; Jianhua Yan (Sustainable Chemistry and Pharmacy, 2026)

Characterization of flavor compounds and core functional microorganisms during pile fermentation of Liupao tea - Yanjun Chen; Yuelan Pang; Yueming Liang; Zhusheng Liu; Zhonghua Liu; Qiming Hu; Fujing Pan (Food Chemistry, 2026)

Hydrolyzed konjac glucomannan retards egg white protein digestion via glycosylation -driven gastric texture and rheology modulation - Lulu Guo; Yicheng Guo; Yating Wu; Shende Hu; Xiaosan Wang; Luping Gu; Cuihua Chang; Junhua Li; Yanjun Yang; Yujie Su (Food Hydrocolloids, 2026)

Development characteristics and hazard mode of loess sinkhole-landslide-mudflow hazard chain: A typical case study of loess tableland - Kai Liu; Xingang Wang; Sheng Hu; Baoqin Lian; Yanjun Li; Daozheng Wang; Haoyu Wang; Chuyi Xu (Engineering Geology, 2026)

New insights into the temporal speciation of phosphorus during anaerobic digestion of wetland biomass wastes - Fan Yu; Junxia Wang; Zhi Wang; Lan Mu; Xutong Wang; Qianqian Guo; Xiaoqiang Cui; Yanjun Hu; Beibei Yan; Guanyi Chen (Bioresource Technology, 2026)

Selective separation of copper and arsenic from actual copper smelting wastewater via sulfurization: a critical review in advantage, competition, parameter, and monitoring - Xiaolu Sun; Yanjun Hu; Yong Liu; Hao Jin; Ning Duan; Linhua Jiang (Journal of Environmental Chemical Engineering, 2026)

Mechanism of EPFRs formation from hydroquinone on transition metal oxide surfaces: coupled experimental and density functional theory study - Junyao Fu; Lingqin Zhao; Aijia Zhang; Guohao Yang; Fan Yu; Yanjun Hu (Waste Disposal & Sustainable Energy, 2026)

Chemical and isotopic constraints on sources of precipitation chemistry in the Yangtze River Delta: A multi-year comparison of mountain and urban sites - Yongbin Jiang; Fei Rong; Guo Hu; Fuchao Zhou; Yanjun Huang; Xiaoyun Wang; Tao Huang; Tao Zhong (Acta Geochimica, 2026)

Chronic heat exposure induces brain atrophy in mice: Molecular signatures and AI-driven intervention strategy - Wenxin Xiang; Bo Yin; Qi Huang; Shisu Li; Miaohui Ding; Guoqing Feng; Ruoran Li; Dizhi Wang; Leizi Min; Xingyuan Hu; Limei Ke; Linfeng Liu; et al. (Journal of Environmental Sciences, 2026)

Dynamics and risk assessment of water conservation in a high-mountain river basin under climate change - Chenhao Chai; Lei Wang; Deliang Chen; Junshui Long; Yanjun Wu; Hu Liu; Jing Zhou; Jingtian Zhang; Chenyuan Hao (Global and Planetary Change, 2026)

Structural characterization, functional properties and formation mechanism of alkali-thermal induced egg white gel: from macroscopic gel properties to molecular conformation and interactions - Shende Hu; Xiaochen Liu; Luping Gu; Cuihua Chang; Junhua Li; Xiaosan Wang; Jun Sun; Shijian Dong; Han Jiao; Yanjun Yang; Yujie Su (Food Research International, 2026)

Magnetic droplet carrier robot integrated with AI-fueled on-site detection - Long Jiao; Wentao Yan; Yanjun Hu; Dongliang Li; Zhenting Xie; Zibing Pan; Qianqian Guo; Xiao Yan; Xiang Wu; Qi Wu (Chemical Engineering Journal, 2026)

Molten salt-assisted Co-pyrolysis of biomass and waste plastics: Analysis of product characteristics - Yanjun Hu; Chong Yang; Fan Yu; Qianqian Guo; Xingxuan Zhang; Wei Bao; Kitae Baek; Rufei Lu; Frederik Ronsse (Biomass and Bioenergy, 2026)

Distinct patterns of intestinal microbiota and immune responses under acute and chronic ammonia stress in yellow catfish (Pelteobagrus fulvidraco) - Kun Xiao; Liling Nie; Shasha Zhao; Gehan Gao; Cuancheng Zhao; Yanjun Du; Rongfei Hu; Ruru Lin; Jie Wang; Man Wang; Dong Han; Lei Zhang (Aquaculture, 2026)

Migration and transformation pathways of Alkali/Alkaline earth metals and chlorine during co-gasification of biochar and Coal: An experimental and thermodynamic analysis - Qianqian Guo; Hongtao Liu; Yanjun Hu; Lu Ding; Long Jiao; Shuai Liu; Xu Wang; Lingqin Zhao; Fan Yu (Fuel, 2026)

Performance analysis and experimental study of flexible opening-closing single garlic seed metering device based on DEM-MBD coupling - Zhengzhong Li; Hua Zhou; Yinping Zhang; Fangyuan Lu; Xian Wang; Jiaye Li; Yanjun Li; Yangting Hu; Rui Yu (Computers and Electronics in Agriculture, 2026)

Liposome-encapsulated egg yolk immunoglobulin (IgY) enhances anti-Helicobacter pylori efficacy by alleviating gastric inflammation, oxidative stress, and regulating gut microbiota - Peixin Song; Zhishuo Zhang; Ruyi Zhang; Wei Hu; Shengqi Rao; Yanjun Yang; Cuihua Chang (Food Bioscience, 2026)

Correction to: Evaluating carbon footprint calculators: a comprehensive assessment framework - Ziqian Xia; Kuang Liu; Jiangnan Li; Yanjun Gu; Bo Hu; Yun Zhong; Jinquan Ye; Ka Leung Lam (Clean Technologies and Environmental Policy, 2026)

Strong tri-genic epistasis among natural alleles of the OsMYB2–OsGH18–OsCAD3 module enhances drought tolerance in rice - Mingyue Huo; Shanwen Wang; Fan Zhang; Min Li; Ming Yin; Yuxin Lei; Yanfang Wang; Yanjun Chen; Dapu Liu; Xiuqin Zhao; Binying Fu; Fengyi Hu; et al. (Molecular Plant, 2026)

Deposition characterization and predictive modeling of phosphorus and heavy metals during sewage sludge incineration - Qianqian Guo; Taojie Duan; Yanjun Hu; Long Jiao; Lingqin Zhao; Fan Yu; Xu Wang; Lei Che; Frederik Ronsse (Journal of Environmental Management, 2026)

The Mesoscopic Mechanisms of Rock Mass Failure under Coupled Blasting and Unloading - Lixiang Xie; Yang Hu; Zhendong Leng; Jianhua Yang; Yanjun Qi; Chao Liu; Wenwei Ma (Rock Mechanics and Rock Engineering, 2026)

Mechanism of Cu migration and transformation during pyrolysis of Copper-Bearing sludge regulated by Cellulose/Kaolinite - Yanjun Hu; Xuan Yu; Lingqin Zhao; Qianqian Guo; Long Jiao; Fan Yu; Aijia Zhang (Waste Management, 2026)

Sustainable N, P co-doped hierarchical porous carbon via coupling phytic acid-melamine assisted hydrothermal carbonization with high temperature activation - Wei Liu; Zhengtong You; Shiqi Qin; Zhipeng Hu; Jiaxin Mu; Zhijun Zhang; Yanjun Xie; Qingwen Wang; Charles U. Pittman (Journal of Environmental Management, 2026)

NADbP: A morphological method to characterize the coupling between landslide evolution and river profile disequilibrium - Ruixin Long; Xiaoyan Zhao; Yanjun Yan; Junhong Hu; Liming Jian (Engineering Geology, 2026)

Freeze-thaw differentially modulates the impact of agricultural film-derived microplastics on soil-crop system: Microbiome and metabolome responses - Yanjun Li; Jiayang Hu; Zhaojiang Liu; Yong Yu (Journal of Hazardous Materials, 2026)

Exploring the potential impact of GPC-enriched egg yolk derivatives on cognitive vitality in aging brains: A preliminary study - Wen Yu; Qing Gao; Yanjun Yang; Cuihua Chang; Wei Hu; Yujie Su; Luping Gu; Junhua Li (Food Bioscience, 2025)

Unveiling the hidden threat: heavy metal accumulation in crops and soil microbial dynamics in a teaching experimental farmland - Xue Gu; Xuegang Yu; Qing Li; Yanjun Mao; Zhiwei Zhou; Huan Hu; Rui Huang; Jiayu Zhou; Yuanyi Sun; Yancheng Li; Aijiang Yang (Plant and Soil, 2025)

Do forestry carbon sinks projects affect grain production? Evidence from China - Yuan Hu; Yanjun Ren; Thomas Glauben; Liangzhi You; Hongxing Lan; Weizhong Zeng (Food Security, 2025)

Sediment dredging effects on nitrogen and phosphorus release in a stratified reservoir: Implications for internal loading management - Yanjun Wu; Hongwei Wang; Zhu Bao; Yunchuang Li; Xiaokang Hu; Chuanzhe Sun; Fanyan Yang; Baoquan Li; Shanshan Liu; Yuyi Wang; Jicheng Zhong (Journal of Environmental Management, 2025)

Polybutylene succinate/fractionated nano lignin@Ag composite films with tunable functions for active food packaging - Shiqi Qin; Zelong Li; Jianpeng Huang; Zhipeng Hu; Wei Liu; Yanjun Xie; Qingwen Wang; Zhijun Zhang (Food Chemistry, 2025)

Chlorination volatilization mechanism for decoupling phosphorus from lead and chromium during sludge incineration - Aijia Zhang; Jing Liu; Yingju Yang; Yanjun Hu; Rundong Li (Chemical Engineering Journal, 2025)

Reliable enrichment monitoring and removal of CrO42− and S2− using multivalent W-doped Ag quantum-dot biomimetic nanozyme - Ruhui Shang; Yanjun Han; Huitian Zhi; Xujie Wang; Yingchao Yang; Xiao Zhu; Lei Hu; Zhengquan Yan (Analytica Chimica Acta, 2025)

Short-term emissions effect of rainfall erosion on soil CO2 in red soil sloped farmland in southern China - Keyu Yan; Xiaohan Mei; Chuan Zhang; Yanmei Hu; Daoxiang Wang; Zhengfa Chen; Xiaofeng Yang; Yanrui Shao; Yanjun Mao (Soil and Tillage Research, 2025)

Agricultural films derived microplastics intensify acetochlor toxicity on soil health - Zhaojiang Liu; Jiayang Hu; Yanjun Li; Yong Yu (Journal of Hazardous Materials, 2025)

Porous Janus membrane for ultrasensitive detection and efficient degradation of sulfur mustard simulant - Meiyang Jin; Shuya Liu; Hailong Jiang; Xia Wang; Yongxian Guo; Yanjun Gong; Qiongzheng Hu; Ru-Song Zhao (Journal of Hazardous Materials, 2025)

CO2 phase fluctuation-induced topological damage enhances shale strength - Changliang Wu; Hongjian Zhu; Yiwen Ju; Zongquan Hu; Yanjun Lu; Ali Raza; Jianchao Cai (International Journal of Rock Mechanics and Mining Sciences, 2025)

Using an integrated model of the extended theory of planned behavior and the temporal self-regulation theory to explain the sugar-sweetened beverage consumption in college students - Zhiqing Hu; Rui Meng; Tongtong Sheng; Qiran Cao; Yanjun Sun; Jian Yin; Yuan He (Appetite, 2025)

Hijacking host phosphate sensing: a new frontier in plant–pathogen warfare - Jiehua Qiu; Feifei Lu; Peisong Hu; Yanjun Kou (Science Bulletin, 2025)

Identifying omitted high reactive VOCs emission sources in China based on new speciated emission inventory - Di Wang; Jinhong Du; Li Yang; Jinmin Zhao; Xinmin Zhang; Zhihao Zhang; Wenjuan Zhao; Weiqi Zhang; Yuzhe Zhang; Jinghua Ma; Wenjing Jin; Yanjun Ren; et al. (Journal of Cleaner Production, 2025)

Magnetic characteristics of sediments in the northern Yangtze River delta since MIS3 and their responses to palaeoenvironmental changes - Guiye Zhang; Longsheng Wang; Xiaohui Wang; Shouyun Hu; Mingming Ma; Jiawen Zhao; Yanjun Ge; Lin Zeng; Xianbin Liu; Chao Zhan; Qing Wang (CATENA, 2025)

Evaluating carbon footprint calculators: a comprehensive assessment framework - Ziqian Xia; Kuang Liu; Jiangnan Li; Yanjun Gu; Bo Hu; Yun Zhong; Jinquan Ye; Ka Leung Lam (Clean Technologies and Environmental Policy, 2025)

Synergistic nano-bioeffects: Dual impact of bisphenol-derived carbon dots on environmental health and antimicrobial therapy - Siyuan Hu; Xinzhong Zhang; Jiayu Li; Xiang Wang; Chen Gao; Jiatong Zhou; Jing Cai; Miaomiao Yin; Rufang Zhao; Xin Ding; Wei Hong; Yanjun Hu (Chemical Engineering Journal, 2025)

Deposition characteristics and genesis of polyhalite in low-grade solid potash ores from the Mahai Salt Lake, Qaidam Basin, China - Pengyu Long; Yanjun Zhao; Yufei Hu; Jiangmin Du (Geosciences Journal, 2025)

Geniposide Improves Corticosterone-induced Toxicity in PC12 Cells through the NMDARs and BDNF Pathway - Qi Ma; Yu Ma; Shizhuo Sun; Lei Yang; Tian Shi; Boxi Zhang; Bo Shang; Ruiyuan Zhou; Jingyuan Liu; Jiao He; Jing Hu; Yanjun Cao (Cell Biochemistry and Biophysics, 2025)

Cysteine and dialysis mediated inhibition of dynamic changes in glycosylated egg white protein during storage - Lulu Guo; Wanqiu Zhang; Fan Zhang; Shende Hu; Qianwen Zhao; Cuihua Chang; Junhua Li; Zijian Huang; Luping Gu; Yanjun Yang; Yujie Su (Food Chemistry, 2025)

The catalytic activity of Ca/Fe-rich incineration ash in the pyrolysis of epidemic wood - Yanjun Hu; Zhenxing Luo; Long Jiao; Caimeng Yu; Jian Li; Qianqian Guo; Jian Song (Waste Disposal & Sustainable Energy, 2025)

Mechanistic insights into the chlorination volatilization of oxidized heavy metals via novel staggered chlorination roasting - Chenglong Lu; Xuan Yu; Guohao Yang; Qianqian Guo; Long Jiao; Jinxiang Lin; Kai Deng; Yanjun Hu (Waste Disposal & Sustainable Energy, 2025)

Melatonin attenuates inflammatory bone loss by alleviating mitophagy and lactate production - Zexin Lin; Yuan Gu; Yingsong Liu; Zilin Chen; Shuai Fang; Zhuan Wang; Zixian Liu; Qingrong Lin; Yanjun Hu; Nan Jiang; Bin Yu; Guanqiao Liu (Apoptosis, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

De novo design of dual-detection fluorescent sensors for bisulfite and copper (II) ion based on cascade activation - Tian Tan; Wenyu Xi; Chenxu Duan; Ying Han; Peikun Xiao; Hongqi Yin; Hong Huang; Xulang Chen; Yanjun Hu; Xiaohuan Huang (Analytica Chimica Acta, 2025)

Impacts of street tree canopy coverage on pedestrians' dynamic thermal perception and walking willingness - Yijuan Sang; Yanjun Hu; Xiao Qin; Hai Yan; Renwu Wu; Fengtao Qian; Xinge Nan; Feng Shao; Zhiyi Bao (Sustainable Cities and Society, 2025)

Metal-loaded biochar catalyzed pyrolysis of wood-plastic composite waste into gasoline and aromatic hydrocarbons - Deshi Yang; Jianpeng Huang; Zhipeng Hu; Wei Liu; Fengqiang Wang; Zhijun Zhang; Yanjun Xie; Qingwen Wang (Fuel, 2025)

A MOF-derived Fe3O4/Fe0/Fe3C-2-600 dual-cathode electro-Fenton system construction: Revealing the mechanism for active centers linked by Fe0 as an electronic transfer station for enhancing Fenton reaction - Chuan Cao; Yanjun Guo; Dadi Chen; Jun Cui; Xiang Hu (Chemical Engineering Journal, 2025)

A dual-branch network for crop-type mapping of scattered small agricultural fields in time series remote sensing images - Yanjun Wu; Zhenyue Peng; Yimin Hu; Rujing Wang; Taosheng Xu (Remote Sensing of Environment, 2025)

L1-Tree: A novel algorithm for constructing 3D tree models and estimating branch architectural traits using terrestrial laser scanning data - Yuhao Feng; Yanjun Su; Jiatong Wang; Jiabo Yan; Xiaotian Qi; Eduardo Eiji Maeda; Matheus Henrique Nunes; Xiaoxia Zhao; Xiaoqiang Liu; Xiaoyong Wu; Chen Yang; Jiamin Pan; et al. (Remote Sensing of Environment, 2024)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Assessing the spatial-temporal impacts of underlying surfaces on 3D thermal environment: A field study based on UAV vertical measurements - Fengtao Qian; Yanjun Hu; Renwu Wu; Hai Yan; Dingsheng Wang; Zhoubing Xiang; Kechun Zhao; Qian Han; Feng Shao; Zhiyi Bao (Building and Environment, 2024)

Establishment of a standardized daily behavior collection and analysis system for brain disease models of rhesus and cynomolgus monkeys and its application in autism spectrum disorder - Xiaofeng Ren; Huimin Wang; Xiaoman Lv; Yi Zhou; Yingyin Fan; Yanjun Yu; Christoph W. Turck; Yuhui Chen; Longbao Lv; Yingzhou Hu; Hao Li; Wenchao Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2024)
Complex brain diseases seriously endanger human health, and early diagnostic biomarkers and effective treatments are currently lacking. Due to ethical constraints on human research, establishing monkey models is crucial to address these issues. With the rapid development of technology, transgenic monkey models of a range of brain diseases, especially autism spectrum disorder (ASD), have been successfully established. However, to establish practical and effective brain disease models and subsequently apply them to disease mechanism and treatment studies, there is still a lack of a standard tool, i.e., a system for collecting and analyzing the daily behaviors of brain disease model monkeys. Therefore, with the goal of undertaking a comprehensive and quantitative study of behavioral phenotypes, we established a standard daily behavior collection and analysis system, including behavioral data collection protocols and a monkey daily behavior ethogram (MDBE) for rhesus and cynomolgus monkeys, which are the most commonly used non-human primates in model construction. Then, we used ASD as an application example after referring to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision (DSM-5-TR), which is widely used in clinical disease diagnosis to obtain ASD core clinical symptoms. We then established a sub-ethogram (ASD monkey core behavior ethogram (MCBE-ASD)) specifically for quantitative assessment of the core clinical symptoms of an ASD monkey model based on MDBE. Subsequently, we demonstrated the high reproducibility of the system.

Hydrodesulfurization kinetic modeling of mixed Feedstocks: An approach using structure-oriented lumping for complex diesel oils - Mengfei Wang; Heping Yang; Xiaowei Bai; Zhenghua Dai; Yunpeng Zhao; Yanjun Hu; Jian Li (Fuel, 2024)

Enhanced co-pyrolysis of textile and leather waste with Ca/Fe-enriched sludge ash: Catalytic effect on thermal behavior, volatile composition, and biochar formation - Yanjun Hu; Zhipeng Xia; Xu Wang; Bo Xing; Qi Chen; Fan Yu; Nan Zhou (Fuel, 2024)

Advancing bioethanol production with a new kinetic model based on structure-oriented lumping for cellulose conversion - Heping Yang; Mengfei Wang; Xiaowei Bai; Zhenghua Dai; Yunpeng Zhao; Yanjun Hu; Jian Li (Fuel, 2024)

Timescale dependent homogeneous assembly of lipid-polymer hybrid nanoparticles in laminar mixing for enhanced lung cancer treatment - ShiXin Li; Bing Yang; Liang Ye; ShuQi Hu; BenHong Li; Yanjun Yang; XiaoBin Jia; Liang Feng; ZhiWei Xiong (Chemical Engineering Journal, 2024)

Mechanochromic luminescent material with high quantum yield for multi-mode anti-counterfeiting applications - Yongxian Guo; Aoli Wu; Qiaoru Zhang; Mei Zhao; Yanjun Gong; Shuya Liu; Mashooq Khan; Haoyang Song; Juyoung Yoon; Qiongzheng Hu (Chemical Engineering Journal, 2024)

Synergetic effects during co-pyrolysis of waste textiles and Ca/Fe-rich industrial sewage sludge: Reaction kinetics and product distribution - Xu Wang; Nan Zhou; Qianqian Guo; Zhenxing Luo; Zhipeng Xia; Yanjun Hu (Waste Management, 2024)

Generation and persistency of combustion-derived environmentally persistent free radicals from phenolic compounds over a Fe2O3/SiO2 surface - Yanjun Hu; Guohao Yang; Nan Zhou; Long Jiao; Lei Wang; Jianhua Yan (Chemosphere, 2024)

Which street is hotter? Street morphology may hold clues -thermal environment mapping based on street view imagery - Yanjun Hu; Fengtao Qian; Hai Yan; Ariane Middel; Renwu Wu; Minghui Zhu; Qian Han; Kechun Zhao; Han Wang; Feng Shao; Zhiyi Bao (Building and Environment, 2024)

Investigation on Uplift Behavior of Rock-Socketed Belled Piles in Horizontal and Inclined Ground Using 1-g Model Test and 3D Numerical Method - Qinke Wang; Zhongbo Hu; Yanjun Guo; Yukun Ji; Baolong Zhu; Jianlin Ma (Rock Mechanics and Rock Engineering, 2024)

Associations between per- and polyfluoroalkyl substances exposure and thyroid hormone levels in the elderly - Kai Tan; QingQuan Zhang; Yanjun Wang; Chunfang Wang; Chongfang Hu; Lin Wang; Hualin Liu; Zhiqiang Tian (Science of The Total Environment, 2024)

High-purity H2 production from mixed PVC/PET plastic wastes through tandem hydrothermal depolymerization and aqueous phase reforming - Hongcai Su; Yuheng Wu; Jie Pan; Lingjun Zhu; Shurong Wang; Yanjun Hu (Process Safety and Environmental Protection, 2024)

Bioavailability transition path of phosphorus species during the sewage sludge incineration process - Qianqian Guo; Yanan Wang; Lingqin Zhao; Fan Yu; Zehuang Zhang; Nan Zhou; Long Jiao; Yanjun Hu (Environmental Research, 2024)

Spatial-temporal variations and drivers of the compound dry-hot event in China - Yanjun Hu; Wen Wang; Peng Wang; Adriaan J. Teuling; Ye Zhu (Atmospheric Research, 2024)

Tetramethylpyrazine inhibits the inflammatory response by downregulating the TNFR1/IκB-α/NF-κB p65 pathway after spinal cord injury - Gang Liu; Luyao Huo; Bowen Deng; Shengyuan Jiang; Yi Zhao; Yanjun Mo; Huizhong Bai; Lin Xu; Chuanyu Hu; Xiaohong Mu (Toxicology and Applied Pharmacology, 2024)

Low temperature and facile synthesis of nitrogen-doped hierarchical porous carbon derived from waste polyethylene terephthalate for efficient CO2 capture - Shaojie Zhou; Haiyang Xu; Shurong Wang; Hongyu Feng; Yanjun Hu; Shicheng Zhang (Science of The Total Environment, 2024)

Non-negligible contribution from coastal erosion to sedimentation around the archipelago: A case study of Miaodao Archipelago - Rijun Hu; Wenkai Liu; Jingrui Li; Bo Liu; Longhai Zhu; Yanjun Yin; Jiandong Qiu; Zhaohan Yi; Jun Ye; Xiaodong Zhang (Marine Geology, 2024)

Improving the evapotranspiration estimation by considering the effect of flux footprint climatology - Jiang Bian; Xiaolong Hu; Liangsheng Shi; Leilei Min; Yucui Zhang; Yanjun Shen; Fenghua Zhao; Yuanyuan Zha; Xie Lian; Jiesheng Huang (Journal of Hydrology, 2024)

Pore structure-dependent sieving effect of mesoporous carbon to mitigate the interference of natural organic matter for selective sulfamethoxazole removal from wastewater - Jiajun Zou; Yanjun Shao; Xinyu Hu; Haichuan Zhang; Shanshan Ye; Ji Li (Chemical Engineering Journal, 2024)

A comparison of hydrothermal carbonization versus pyrolysis-activation for sludge-derived carbon materials on physiochemical properties and electrochemical performance - Qianqian Guo; Shixuan Qiao; Dongming Zhang; Zehuang Zhang; Fan Yu; Zhongqing Ma; Yanjun Hu (Biomass and Bioenergy, 2024)

Fine-tuning bromide AIE probes for Hg2+ detection in mitochondria with wash-free staining - Tian Tan; Chuang Zhang; Ying Han; Ruijun Chu; Wenyu Xi; Xulang Chen; Jingyu Sun; Hong Huang; Yanjun Hu; Xiaohuan Huang (Journal of Hazardous Materials, 2024)

Upcycling MSWI fly ash into green binders via flue gas-enhanced wet carbonation - Miao Lu; Weizhe Ge; Yan Xia; Chen Sun; Xiaoqing Lin; Daniel C.W. Tsang; Tung-Chai Ling; Yanjun Hu; Lei Wang; Jianhua Yan (Journal of Cleaner Production, 2024)

Catalytic conversion of lignin into monoaromatic hydrocarbons over a Ni/Al hydrotalcite-derived catalyst - Deshi Yang; Jianpeng Huang; Zhipeng Hu; Yuanyuan Miao; Fengqiang Wang; Zhijun Zhang; Yanjun Xie; Shouxin Liu; Qingwen Wang; Charles U. Pittman (Fuel, 2024)

Catalytic stepwise pyrolysis for dechlorination and chemical recycling of PVC-containing mixed plastic wastes: Influence of temperature, heating rate, and catalyst - Yanjun Hu; Mingzhe Li; Nan Zhou; Hao Yuan; Qianqian Guo; Long Jiao; Zengyi Ma (Science of The Total Environment, 2024)

Ultra-stretchable, sensitive and breathable electronic skin based on TPU electrospinning fibrous membrane with microcrack structure for human motion monitoring and self-powered application - Yu Tian; Mengjie Huang; Yalong Wang; Yanjun Zheng; Rui Yin; Hu Liu; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Release behavior of soluble salts in MSWI bottom ash used as road basement materials under continuous rainfall conditions - Lingqin Zhao; Dongming Zhang; Yanjun Hu; Qianqian Guo; Long Jiao; Nan Zhou; Francesco Di Maio (Waste Disposal & Sustainable Energy, 2023)

Achieving grain security and carbon neutrality: Challenges from carbon allocation - Fan Liu; Yucui Zhang; Xingchang Wang; Yongqing Qi; Leilei Min; Guirui Yu; Chunsheng Hu; Yanjun Shen (Journal of Cleaner Production, 2023)

Hygrothermal and energy performance assessment of a passive building wall integrating PCM and bio-based hygroscopic material - Dongxia Wu; Mourad Rahim; Wendong Li; Mohammed El Ganaoui; Rachid Bennacer; Kaiyong Hu; Huan Sun; Zhili Sun; Tonghua Zou; Yanjun Zhang (Building and Environment, 2023)

Alternative scenarios for urban tree surveys: Investigating the species, structures, and diversities of street trees using street view imagery - Yanjun Hu; Han Wang; Hai Yan; Qian Han; Xinge Nan; Kechun Zhao; Zhiyi Bao (Science of The Total Environment, 2023)

Highly sensitively detection of amine vapors released during shrimp spoilage by fluorescent molecules locked in covalent organic frameworks - Jingru Mi; Yongxian Guo; Yanjun Gong; Shuya Liu; Mei Zhao; Qiongzheng Hu; Li Yu (Food Chemistry, 2023)

Adaptive corrected parameters algorithm applied in cooling load prediction based on black-box model: A case study for subway station - Yuanyang Hu; Luwen Qin; Shuhong Li; Xiaohuan Li; Runfa Zhou; Yanjun Li; Wei Sheng (Energy and Buildings, 2023)

Mechanism of adsorption capacity enhancement of coal due to interaction with high-pressure scCO2-water system - Siyuan Liu; Chuanjie Zhu; Yanjun Li; Sijia Hu; Xiangliang Zhang; Cong Ma (Gas Science and Engineering, 2023)

An integrated slot allocation model for time-space-dimensional noise reduction - Huilin Feng; Rong Hu; Junfeng Zhang; Yanjun Wang; Yutong Zhang (Transportation Research Part D: Transport and Environment, 2023)

Dynamic effects of miR-20a-5p on hippocampal ripple energy after status epilepticus in rats - Xinyu Zhang; Yanjun Yi; Li Cheng; Hengsheng Chen; Yue Hu (Experimental Brain Research, 2023)

Cobalt induces neurodegeneration through FTO-triggered autophagy impairment by targeting TSC1 in an m6A-YTHDF2-dependent manner - Jianping Tang; Fuli Zheng; Xu Liu; Yanjun Li; Zhenkun Guo; Xinpei Lin; Jinfu Zhou; Yu Zhang; Guangxia Yu; Hong Hu; Wenya Shao; Siying Wu; et al. (Journal of Hazardous Materials, 2023)

A novel reutilization of ash from biomass gasification process: Feasibility and products improvement analysis - Qianqian Guo; Beibei Yan; Yanjun Hu; Xiang Guo; Wenzhu Wu; Zhanjun Cheng; Guanyi Chen; Li'an Hou (Fuel, 2023)

Identification and transcriptome data analysis of ARF family genes in five Orchidaceae species - Yiwei Bai; Yanjun Ma; Yanting Chang; Wenbo Zhang; Yayun Deng; Na Zhang; Xue Zhang; Keke Fan; Xiaomeng Hu; Shuhua Wang; Zehui Jiang; Tao Hu (Plant Molecular Biology, 2023)

The Potential of NLRP3 Inflammasome as a Therapeutic Target in Neurological Diseases - Wenfang He; Zhiping Hu; Yanjun Zhong; Chenfang Wu; Jinxiu Li (Molecular Neurobiology, 2023)

Managing iodine and tin based defects for efficient and stable mixed Sn-Pb perovskite solar cells - Yanjun Xing; Zhiqiang Deng; Tonghui Guo; Zequn Zhang; Qidong Tai; Rui Zhao; Jiaxing Xiong; Qiuxiang Wang; Like Huang; Xiaohui Liu; Ziyang Hu; Yuejin Zhu; et al. (Chemical Engineering Journal, 2023)

Low-temperature upcycling of PET waste into high-purity H2 fuel in a one-pot hydrothermal system with in situ CO2 capture - Hongcai Su; Tian Li; Shurong Wang; Lingjun Zhu; Yanjun Hu (Journal of Hazardous Materials, 2023)

Mapping China’s planted forests using high resolution imagery and massive amounts of crowdsourced samples - Kai Cheng; Yanjun Su; Hongcan Guan; Shengli Tao; Yu Ren; Tianyu Hu; Keping Ma; Yanhong Tang; Qinghua Guo (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Transparent, intrinsically stretchable cellulose nanofiber-mediated conductive hydrogel for strain and humidity sensing - Ziyu Bian; Yinghui Li; Hongling Sun; Mengyu Shi; Yanjun Zheng; Hu Liu; Chuntai Liu; Changyu Shen (Carbohydrate Polymers, 2023)

Mixed heavy metals exposure affects the renal function mediated by 8-OHG: A cross-sectional study in rural residents of China - Xiaoyu Tian; Xiaobing Shan; Li Ma; Chenyang Zhang; Mei Wang; Jie Zheng; Ruoyi Lei; Li He; Jun Yan; Xun Li; Yanjun Bai; Keqin Hu; et al. (Environmental Pollution, 2023)

Distribution and transport of heavy metals in surface sediments of Chengbei Sea in the Bohai Sea - Zhiyu Lei; Rijun Hu; Xiaodong Zhang; Longhai Zhu; Yanjun Yin; Bo Liu; Xiaodong Yuan (Environmental Science and Pollution Research, 2022)

Quantification and distribution of extractable metals of MSWI bottom ash in view of its valorization in China - Yanjun Hu; Lingqin Zhao; Qianqian Guo; Lianming Li; Yihong Wang; Yufan Ye; Fuzhi Mao; Wangyang Tian (Waste Disposal & Sustainable Energy, 2022)

The edited UPF1 is correlated with elevated asparagine synthetase in pancreatic ductal adenocarcinomas - Jiayang Hu; Zhen Wang; Shunchao Yang; Yanjun Lu; Gang Li (Molecular Biology Reports, 2022)

Investigation on oxygen-controlled sewage sludge carbonization with low temperature: from thermal behavior to three-phase product properties - Fan Yu; Yanjun Hu; Lianming Li; Qianqian Guo; Yonghao Zhu; Long Jiao; Yihong Wang; Xiaoqiang Cui (Environmental Science and Pollution Research, 2022)

Identification of Benign and Malignant Lung Nodules in CT Images Based on Ensemble Learning Method - Yifei Xu; Shijie Wang; Xiaoqian Sun; Yanjun Yang; Jiaxing Fan; Wenwen Jin; Yingyue Li; Fangchu Su; Weihua Zhang; Qingli Cui; Yanhui Hu; Sheng Wang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Investigation on Reservoir Stimulation Characteristics in Hot Dry Rock Geothermal Formations of China During Hydraulic Fracturing - Yuxiang Cheng; Yanjun Zhang; Ziwang Yu; Zhongjun Hu (Rock Mechanics and Rock Engineering, 2021)

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

Study on the Coincident-Loop Transient Electromagnetic Method in Seafloor Exploration—Taking Jiaodong Polymetallic Mine as a Model - Yixing Ma; Junhua Hu; Yanjun Chang; Zujian Liu (Journal of Earth Science, 2021)

Dexmedetomidine had neuroprotective effects on hippocampal neuronal cells via targeting lncRNA SHNG16 mediated microRNA-10b-5p/BDNF axis - Li Wang; Weihua Liu; Yanjun Zhang; Zhanfei Hu; Hao Guo; Jingshu Lv; Hongyin Du (Molecular and Cellular Biochemistry, 2020)
Dexmedetomidine (DEX), a highly selective alpha2 adrenergic receptor agonist, is a commonly used anesthetic drug in surgical procedures. Previous studies have indicated that DEX exerts neuroprotective effects while the detailed mechanism has not been fully elucidated. Here, we aim to study the role of lncRNA SHNG16 in DEX-induced brain protection and its underlying molecular mechanism. The rats underwent middle cerebral artery occlusion (MCAO) surgery and oxygen–glucose deprivation (OGD)-treated HT22 hippocampal neurons were treated with DEX, respectively. CCK8 was used to evaluate cell viability. sh-SHNG16 as well as miR-10b-5p mimics were transfected into hippocampal neurons to further explore the bio-function of SNHG16 and miR-10b-5p in vitro. Furthermore, the interactions between SHNG16 and miR-10b-5p, miR-10b-5p and BDNF gene were confirmed by dual-luciferase report assay. Our data revealed that DEX attenuated neurological damage of the MCAO rats and also increased the cell viability of the neurons significantly. Besides, expression of SHNG16 and BDNF were both downregulated while miR-10b-5p was upregulated in MCAO brain tissues or OGD treated neurons. DEX inhibited miR-10b-5p expression but increased SHNG16 and BDNF levels with a dosage effect. After transfection with sh-SHNG16 or miR-10b-5p mimics, the expression of BDNF protein was downregulated, accompanied with decreased neuron viability. Dual-luciferase assay showed that SHNG16 targeted on miR-10b-5p, which also could bind directly to the 3′-UTR sites of BDNF and negatively regulate its expression. In conclusion, DEX exerts neuroprotective in ischemic stroke via improving neuron damage, the underlying mechanism may be upregulating SHNG16 and BDNF via sponging miR-10b-5p.

Drought-induced disturbance of carbohydrate metabolism in anthers and male abortion of two Gossypium hirsutum cultivars differing in drought tolerance - Wei Hu; Yanjun Huang; Dimitra A. Loka; Hua Bai; Yu Liu; Shanshan Wang; Zhiguo Zhou (Plant Cell Reports, 2020)

Spatiotemporal Variations and Regional Transport of Air Pollutants in Two Urban Agglomerations in Northeast China Plain - Xiaolan Li; Xiaoming Hu; Shuaiyi Shi; Lidu Shen; Lan Luan; Yanjun Ma (Chinese Geographical Science, 2019)

Identification of movement characteristics and causal factors of the Shuping landslide based on monitored displacements - Qiong Wu; Huiming Tang; Xiaohan Ma; Yiping Wu; Xinli Hu; Liangqing Wang; Robert Criss; Yi Yuan; Yanjun Xu (Bulletin of Engineering Geology and the Environment, 2019)

Follicular helper T cell and memory B cell immunity in CHC patients - Yong Liu; Huifan Ji; Pingwei Zhao; Hongqing Yan; Yanjun Cai; Lei Yu; Xiaoli Hu; Xiguang Sun; Yanfang Jiang (Journal of Molecular Medicine, 2019)

Transplantation of UC-MSCs on collagen scaffold activates follicles in dormant ovaries of POF patients with long history of infertility - Lijun Ding; Guijun Yan; Bin Wang; Lu Xu; Yan Gu; Tong Ru; Xiaoying Cui; Lei Lei; Jingyu Liu; Xiaoqiang Sheng; Bin Wang; Chunxue Zhang; et al. (Science China Life Sciences, 2018)

Ectopic expression of cucumber (Cucumis sativus L.) CsTIR/AFB genes enhance salt tolerance in transgenic Arabidopsis - Zhehao Chen; Mengting Li; Ye Yuan; Jiangqin Hu; Yanjun Yang; Jiliang Pang; Lilin Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

An integrated UAV-borne lidar system for 3D habitat mapping in three forest ecosystems across China - Qinghua Guo; Yanjun Su; Tianyu Hu; Xiaoqian Zhao; Fangfang Wu; Yumei Li; Jin Liu; Linhai Chen; Guangcai Xu; Guanghui Lin; Yi Zheng; Yiqiong Lin; et al. (International Journal of Remote Sensing, 2017)

Altitude variation in chilling tolerance among natural populations of Elymus nutans in the Tibetan Plateau - Juanjuan Fu; Yuefei Xu; Yanjun Miao; Tianming Hu (Acta Physiologiae Plantarum, 2016)

Forest fuel treatment detection using multi-temporal airborne lidar data and high-resolution aerial imagery: a case study in the Sierra Nevada Mountains, California - Yanjun Su; Qinghua Guo; Brandon M. Collins; Danny L. Fry; Tianyu Hu; Maggi Kelly (International Journal of Remote Sensing, 2016)

Transgenic analysis reveals LeACS-1 as a positive regulator of ethylene-induced shikonin biosynthesis in Lithospermum erythrorhizon hairy roots - Rongjun Fang; Fengyao Wu; Ailan Zou; Yu Zhu; Hua Zhao; Hu Zhao; Yonghui Liao; Ren-Jie Tang; Tongyi Yang; Yanjun Pang; Xiaoming Wang; Rongwu Yang; et al. (Plant Molecular Biology, 2016)

Exploration of genetic diversity among medicinally important genus Epimedium species based on genomic and EST-SSR marker - Zubaida Yousaf; Weiming Hu; Yanjun Zhang; Shaohua Zeng; Ying Wang (Natural Product Research, 2015)

Exploiting the Role of Resveratrol in Rat Mitochondrial Permeability Transition - Yue Zhang; Fangfang Tian; Qi Xiao; Yanjun Hu; Jiahan Li; Fenglei Jiang; Yi Liu (The Journal of Membrane Biology, 2013)

Analysis of molecular variation of porcine reproductive and respiratory syndrome virus in Central China from 2006 to 2012 - Yuejun Shi; Zhibin Hu; Zhenghui Xiong; Yanjun Zhou; Xin Jin; Changqin Gu; Xueying Hu; Guofu Cheng; Nianhua Song; Wanpo Zhang (Archives of Virology, 2013)

A comparison study of the simulation accuracy between WRF and MM5 in simulating local atmospheric circulations over Greater Beijing - ZhenXin Liu; ShuHua Liu; Fei Hu; Ju Li; YanJun Ma; HePing Liu (Science China Earth Sciences, 2012)

Whole genome sequencing of lamb rotavirus and comparative analysis with other mammalian rotaviruses - Yanjun Chen; Weiwen Zhu; Shuo Sui; Yuxin Yin; Songnian Hu; Xiaowei Zhang (Virus Genes, 2009)

Improvement in growth and toxin production of Alexandrium tamarense by two-step culture method - Hanhua Hu; Yanjun Shi; Wei Cong (Journal of Applied Phycology, 2006)

Improved use of organic phosphate by Skeletonema costatum through regulation of Zn2 + concentrations - Yanjun Shi; Hanhua Hu; Runyu Ma; Wei Cong; Zhaoling Cai (Biotechnology Letters, 2004)

Growth and photosynthesis limitation of marine red tide alga Skeletonema costatum by low concentrations of Zn2+ - Hanhua Hu; Yanjun Shi; Wei Cong; Zhaoling Cai (Biotechnology Letters, 2003)